RANCANG BANGUN SISTEM INFORMASI DATA POKOK PENDIDIKAN (DAPODIK) MUHAMMADIYAH - Andri Wahyudi; Andre Himawan; Kinanti Trisna (Informatics and Computer Engineering Journal, 2022)
Information technology touches various aspects of the government sector and makes everything easier so that the data obtained can be processed faster and saves more time. One of those who get convenience with the development of this information technology is the organization. Muhammadiyah is a social organization that focuses on various fields, one of which is education. Therefore, it is very necessary to have a centralized and digital basic education data system (Dapodik) in data collection for Muhammadiyah Educational Institutions. A design design of the Muhammadiyah education basic data information system as a reference for the Educational Education Council to be a consideration for the importance of this system. Program Design Methods are needed to facilitate communication between the system and users. In the interface that the author designed to become a proposed system, there are 3 types, namely the frontend interface, the school account backend interface and the database account backend interface. Dapodik Muhammadiyah is one way to overcome the data collection problem experienced by the PP Muhammadiyah Educational Education Council. As well as helping many people to find information about Education Data, Teacher Data, Student Data and Employee Data.